Characteristics, Roles and Challenges of Traffic Personnel: Implications toward Efficient Traffic Management System (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this study was to determine the characteristics, roles and challenges of traffic personnel and their implications toward efficient traffic management system in Bacolod City during the second quarter of calendar year 2018. A mixed methods research design was used which involved the use of both quantitative and qualitative methods by means of survey responded by 150 traffic personnel, key informant interview participated by 3 Barangay Captains and a City Councilor, and focus group discussion participated by 6 traffic personnel which were all selected through a purposive and convenience sampling techniques. Frequency count, percentage, weighted mean, standard deviation, Mann- Whitney U, Kruskal Wallis and IBM SPSS Version 19 were employed to analyze and present the data for quantitative part. While the qualitative part of the study, Thematic Analysis was utilized. The findings showed that traffic personnel who participated in the study were almost equally divided when grouped according to age, while majority were male, attained college level, have less than 7 years of experience and designated as traffic enforcer. Meanwhile, not all completed the required trainings. When it comes to their roles as traffic personnel, it showed that they are mainly managing traffic flow and implementing traffic rules and regulations in the roads. Moreover, it showed that majority of them are highly knowledgeable on City Ordinance 338, and there are no significant differences when they were grouped according to age, sex, educational attainment, and job designation. However, significant differences were found in their level of knowledge on the aforementioned ordinance when they were grouped according to length of service and trainings attended. On the other hand, it was found out that the top most challenge experienced by the participants is the arrogance of drivers. The lack of discipline which includes disregarding of traffic rules and regulations among drivers follows next. Ignorance of the traffic rules and regulations among road users, attitude of drivers, bad weather conditions, high volume of vehicles and road widening projects are also included in the short list of challenges encountered by traffic personnel in the City. Finally, results of this study were used in formulating an enhanced traffic management system program for Bacolod Traffic Authority Office.